2013
DOI: 10.1177/0021998313494101
|View full text |Cite
|
Sign up to set email alerts
|

Out-of-autoclave prepreg consolidation under deficient pressure conditions

Abstract: The present study investigated the effects of three pressure-related process deviations (reduced ambient pressure, reduced vacuum and restricted air evacuation) on the consolidation and quality of flat laminates manufactured by out-of-autoclave prepreg processing. The evolution of laminate thickness, measured in-situ, was correlated with thickness and porosity data for woven and unidirectional fibre bed composites. The process deficiencies are shown to have had distinctive detrimental effects on the rate of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(56 citation statements)
references
References 9 publications
2
54
0
Order By: Relevance
“…It reveals that an evenly distributed flow front, neglecting material variations, results in a void free part. However, when material variations are included, the model predicts the possibility of having a non-zero void content, which is in compliance with experimental data presented in [6].…”
Section: Comparison and Discussion Of Stochastic And Deterministic Mosupporting
confidence: 84%
See 1 more Smart Citation
“…It reveals that an evenly distributed flow front, neglecting material variations, results in a void free part. However, when material variations are included, the model predicts the possibility of having a non-zero void content, which is in compliance with experimental data presented in [6].…”
Section: Comparison and Discussion Of Stochastic And Deterministic Mosupporting
confidence: 84%
“…Not only cure cycle ramp rate, dwell temperature, and out-time affecting the resin viscosity evolution determine the consolidation process [4,5]. Also fibre bed architecture, degree of air evacuation, consolidation pressure differential [6] and moisture content [7] were proven to be relevant for the final part quality, as summarized in [8]. This reveals the importance of capturing all the phenomena and interactions in an OoA process model.…”
Section: Introductionmentioning
confidence: 94%
“…The air initially entrapped in the interply region has likely relocated to the intraply dry area in the sealed configuration. This assumption is supported by a quality study of OoA laminates conducted by Centea and Hubert [4]. They processed prepregs with sealed edges and when compared to laminates processed with full edge breathing, the laminates with sealed edges had an increased void content in the dry intraply area.…”
mentioning
confidence: 88%
“…These studies (e.g. [5,6,15]) were mainly concerned with prediction and experimental evaluation of the final shape of the specimen, especially corner parts, and were able to detect the effect of layup on the shape or the effect of processing conditions on thickness of flat laminates. The latest research [3,16,17] has shown that more advanced models can predict geometry of complex shape specimens.…”
Section: This Paper Employs the Hyper-viscoelastic Consolidation Modementioning
confidence: 99%